Validity of a computational thinking and artificial intelligence-based electronic student worksheet in the context of deforestation - Tampubolon, Farah Nabilah; Hapizah, Hapizah; Meryansumayeka, Meryansumayeka (Jurnal Gantang, 2026)
Indonesian students’ mathematical literacy remains below the OECD average, with international assessments indicating persistent difficulty in translating contextual problems into systematic mathematical reasoning, a gap that Computational Thinking (CT) is theorized to help close. This study examines the validity of a Computational Thinking-based electronic student worksheet (E-LKPD), supported by Artificial Intelligence (AI), in the context of deforestation on the topic of Linear Equation System in Two Variables (SPLDV). The research addresses the need for valid learning tools that strengthen students’ mathematical problem-solving skills while promoting environmental awareness, examining how CT skills and environmental issues can be meaningfully integrated, with AI assisting the algorithmic stage of CT through automated feedback, solution-strategy hints, and adaptive task difficulty. The method used is design research with a development studies approach, focusing on preliminary research and prototyping. Validation involved expert review by subject-matter, media, and education experts, together with one-to-one student evaluations, to assess content, construct, language, and visual aspects. Results show that the CT-based E-LKPD with AI support meets the established validity criteria for content accuracy, presentation, and media quality. The developed E-LKPD is thus feasible for use as a learning tool integrating computational thinking, artificial intelligence, and environmental awareness.